Rekindling individualism, consuming emotions: Constructing "psytizens" in the age of happiness. (September 2016) - Cabanas, Edgar
Happiness has become a new moral regime in neoliberal societies that defines what is right and wrong and stresses the insource of responsibility. More importantly, happiness stands out as a new model of selfhood that aligns with the neoliberal ideology of individualism and consumerism at the same time that legitimizes and rekindles this same ideology in seemingly nonideological terms through the discourse of science. The paper claims that this model of selfhood turns citizens into psytizens, that is, into psychological clients whose full functionality as individuals is largely tied to the pursuing, consuming, and development of their own happiness. The paper analyzes this notion of psytizen and its three main features, comments upon the happiness industry that simultaneously presupposes and targets this model of selfhood, and examines the role that happiness studies, in general, and positive psychology, in particular, play in shaping this emerging notion of citizenship.